Periviable Birth: Executive Summary of a Joint Workshop by the Eunice Kennedy Shriver National Institute of Child Health and Human Development, Society for Maternal-Fetal Medicine, American Academy of Pediatrics, and American College of Obstetricians and Gynecologists. Issue 2 (June 2015) - Raju, T.N.; Mercer, B.M.; Burchfield, D.J.; Joseph, G.F.
Abstract : ( Obstet Gynecol . 2014;123(5):1083–1096)